2015
DOI: 10.1097/acm.0000000000000736
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing Residents’ Competence

Abstract: Institutions orient resident performance review toward problem identification; a developmental approach is uncommon. Clarifying the purpose of resident performance review and employing efficient information systems that synthesize performance data and engage residents and faculty in purposeful feedback discussions could enable the meaningful implementation of milestones-based assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(57 citation statements)
references
References 19 publications
(17 reference statements)
0
57
0
Order By: Relevance
“…The large volume of diverse data produced, in turn, requires new processes of assembly and analysis. In response to this need, postgraduate medical programmes in Canada and the USA have integrated new group decision‐making bodies, referred to as Clinical Competency Committees (CCCs), into their programmes of assessment . These small groups operate as centralised review bodies that conduct in‐depth reviews of diverse assessment data collected about trainee performance and use collective processes to render decisions about progression …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The large volume of diverse data produced, in turn, requires new processes of assembly and analysis. In response to this need, postgraduate medical programmes in Canada and the USA have integrated new group decision‐making bodies, referred to as Clinical Competency Committees (CCCs), into their programmes of assessment . These small groups operate as centralised review bodies that conduct in‐depth reviews of diverse assessment data collected about trainee performance and use collective processes to render decisions about progression …”
Section: Introductionmentioning
confidence: 99%
“…This type of small group decision making is no small task. Committees must sift through large amounts of quantitative and qualitative performance data, interpret their meanings, and create an intelligible composite that reliably communicates the trainee's competencies . This process relies on the expertise and judgement of committee members and their ability to interpret performance evidence and transform it into a decision about trainee competence.…”
Section: Introductionmentioning
confidence: 99%
“…A 2015 qualitative analysis of 34 CCCs by Hauer et al (8) found that most committees were oriented toward a ‘problem-identification’ model, in which the committee members’ efforts focused on searching performance data for ‘red-flags’ to identify struggling residents. In this model, records of residents with performance issues were reviewed in detail for other events, while residents without issues were minimally reviewed, if at all.…”
Section: The Problem and Ways To Approach Itmentioning
confidence: 99%
“…However, a few programs pursued what was characterized as a ‘developmental’ model, in which CCCs compared all residents’ performance data against established benchmarks, with focused discussion on areas for resident growth. Those using a developmental model identified concerns of increased time for the CCCs to apply the complex milestone format and the need for faculty development in qualitative methods as potential implementation challenges (8). …”
Section: The Problem and Ways To Approach Itmentioning
confidence: 99%
See 1 more Smart Citation